Sistem Informasi Penjualan Mainan Menggunakan Algoritma Single Moving Average Berbasis Web Pada Rumah Hotwheels Karawang - Muhammad Yazid; Dwipa Handayani; Prima Dina Atika (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2026)
This study discusses the development of a web-based sales information system for Rumah Hotwheels Karawang by implementing the Single Moving Average (SMA) method to forecast inventory requirements. The system was developed to overcome problems related to manual transaction recording and inventory management. The application was developed using the Waterfall method and implemented with PHP and MySQL. Historical sales data were processed using the SMA algorithm to generate sales forecasts that support inventory management decisions. Black-box testing results showed that all system features, including inventory management, sales transactions, reporting, and forecasting, functioned according to user requirements. The system helps improve inventory management efficiency while reducing the risk of stock shortages and overstocking.